PHBS Implementation in Pondok Pesantren During Covid-19 Pandemic In Kediri East Java, Indonesia, 2021 (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
During the Covid-19 Pandemic, Pondok Pesantren environment can be a risky place for disease transmission because Pondok Pesantren are places where students gather in one room, such as sleeping, eating, studying and using shared bathrooms. With the condition of Pondok Pesantren with inadequate health support facilities and clean and healthy living behaviors that have not become the daily habits of the students, it takes commitment from the Pesantren Leaders and the active role of all students to make efforts to prevent disease transmission which can be done by increasing the application of Perilaku Hidup Bersih dan Sehat (PHBS). PHBS is a set of behaviors that are practiced such as washing hands with soap, wearing masks, not smoking, consuming balanced nutrition, staying in the boarding school, avoiding crowds, keeping the environment clean and others, on the basis of awareness as a result of learning that makes the pesantren community able to helping himself to play an active role in preventing the transmission of COVID-19 to realize the health of the pesantren community. The purpose of this activity is to establish cross-sectoral partnerships in increasing the knowledge and awareness of students and all residents of Pondok Pesantren in the application of PHBS. The methods used are surveys, needs analysis and health education. The result of this activity is the willingness and ability of the Pondok pesantren community in implementing PHBS and health protocols, especially during the COVID-19 pandemic.